Dapatkah Orientasi Digital dan Orientasi Wirausaha Berperan Dalam Meraih Keunggulan Kompetitif Dalam Bisnis Coffee Shop ? - Afifah, Afifah; Gustiawan, Willson; Sari, Maya Permata; Septivani, Mega Dwi; Rachmi, Feny Melia (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
This research delves into how digital and entrepreneurial focus contribute to gaining an edge, for coffee shops in Bukittinggi and Payakumbuh areas.The study employs a survey approach by gathering information from 115 coffee shop proprietors or supervisors in these regions.The findings reveal a correlation between emphasis and competitive advantage suggestive of the significance of utilizing digital tools and tactics for business prosperity. Moreover the study indicates that while entrepreneurial orientation is positively influential it has an impact compared to the emphasis, on strategies. It implies that although having an entrepreneurial mindset is crucial, in the coffee shop industry todays landscape requires businesses to embrace transformation to stay ahead of the curve. The data was examined utilizing. The results underscore the significance of utilizing technology for long term development and establishment as a market leader.